1993
DOI: 10.1002/ajmg.1320450617
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve abnormalities in CHARGE association

Abstract: Many children with the CHARGE association have facial paralysis and feeding and swallowing difficulties. Indeed, facial paralysis and pharyngeal incoordination may be important diagnostic indicators of CHARGE association [Davenport et al., 1986a; Mitchell et al., 1985]. We describe an individual with dysfunction of multiple cranial nerves (Möbius sequence) and CHARGE association, a previously unrecognized combination. Our review of 150 patients from the literature and 13 patients from this center with CHARGE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…This is consistent with recent findings [Chalouhi et al, 2003] and others [Lin et al, 1990;Byerly and Pauli, 1993].…”
supporting
confidence: 94%
“…This is consistent with recent findings [Chalouhi et al, 2003] and others [Lin et al, 1990;Byerly and Pauli, 1993].…”
supporting
confidence: 94%
“…Recently, Vissers et al [2] demonstrated that mutations or deletions of the gene CHD7 in chromosome region 8q12 are responsible for the birth defects seen in CHARGE syndrome. Multiple cranial nerve dysfunction is common in patients with CHARGE, with over three-quarters having evidence of cranial nerve dysfunction [3]. As many as nine out of 10 children with CHARGE syndrome have feeding difficulties [4], which some authors attribute to dysfunction of the glossopharyngeal and vagus nerves [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Aspiration was suspected in 47% of children with CHARGE syndrome who had ''recurrent chest infections'', and pulmonary disease was felt to contribute to seven of 17 deaths in a study of lung involvement in CHARGE syndrome [7]. More generalized ''feeding difficulties'' are noted in nearly all children with CHARGE syndrome, often resulting in long-term enteral feeding or placement of a gastrostomy tube [3,5,[8][9][10]. More recently, Roger et al [9] noted aspiration in 31 of 42 children with CHARGE syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Blake et al 7 added cranial nerve anomalies to the list of major criteria, emphasizing the frequency of such anomalies as facial palsy (VII), sensory neural hearing loss (VIII), and swallowing difficulties (IX, X). 9 He also modified the status of characteristic ear anomalies, including them among the major criteria, and he added a host of less specific but frequent minor criteria.…”
mentioning
confidence: 99%